Dinamika Penggunaan Bahasa Indonesia Di Media Sosial: Analisis Literatur - Rina Ari Rohmah (CV.Karoteh Utama, 2024)
This study examines the dynamics of Indonesian language use on social media through a meta-analysis of relevant literature. Social media serves as a dynamic communication platform, influencing language use in terms of form, meaning, and politeness. The findings reveal an increasing use of slang, code-switching between Indonesian and foreign languages, and frequent language errors, particularly among the younger generation. This phenomenon poses a threat to the preservation of Indonesian as a national identity. However, social media also provides opportunities to promote proper language use through educational campaigns and the utilization of digital platforms for learning. Therefore, balancing language preservation and adapting to global trends is crucial. This study recommends collaboration among educational institutions, policymakers, and communities to raise awareness about proper Indonesian language use in the digital era.